1998
DOI: 10.1039/a707868d
|View full text |Cite
|
Sign up to set email alerts
|

Electrospray mass spectrometry of metal carbonyl complexes †

Abstract: Methods are described for characterising neutral metal carbonyl complexes using electrospray mass spectrometry, by converting them into ions with suitable reagents. Ionisation techniques included addition of OMe Ϫ generating [M ϩ OMe] Ϫ species, addition of Ag ϩ or Na ϩ ions giving the appropriate positive ion, abstraction of acidic hydrogen forming [M Ϫ H] Ϫ ions, or (in rare cases) oxidation giving radical cations [M] ϩ . The methods can be used on pure compounds or on mixtures. Fragmentation in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
144
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 159 publications
(146 citation statements)
references
References 42 publications
2
144
0
Order By: Relevance
“…16 The m/z values reported are the strongest in the isotope envelope, and formulations were confirmed by matching isotope patterns with simulated ones generated with ISOTOPE. 30 Fast atom bombardment mass spectra were obtained on a JEOL SX-102 spectrometer using 3-nitrobenzyl alcohol as matrix and CsI as calibrant.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…16 The m/z values reported are the strongest in the isotope envelope, and formulations were confirmed by matching isotope patterns with simulated ones generated with ISOTOPE. 30 Fast atom bombardment mass spectra were obtained on a JEOL SX-102 spectrometer using 3-nitrobenzyl alcohol as matrix and CsI as calibrant.…”
Section: Discussionmentioning
confidence: 81%
“…16,21 Both of these ions were remarkably robust, undergoing CO loss only at high cone voltages, >60 V, and in contrast to the very ready loss of Ph 3 Sn + from 1, there was no indication at all of a similar process for 5.…”
Section: Methodsmentioning
confidence: 99%
“…Chemical aids to ionisation were used. 34 Elemental analyses were by CMAS, Belmont, Vic., Australia.…”
Section: Methodsmentioning
confidence: 99%
“…The corresponding cluster k values of the fragment should be on the increase. Very interesting extensive work on the metal carbonyls that involves stripping off the CO ligands has been done by several research groups (Butcher, et al, 2002(Butcher, et al, , 2003Crawford, et al, 2006;Critchley, et al, 1999;Dyson, et al, 2001;Henderson, et al, 1998Henderson, et al, , 2009 Table 7). Although the series and the skeletal numbers predict that each of the Re skeletal atoms except one should have a hydrogen atom, the structural determination indicates all the hydrogen atoms are bridging (Miessler, et al, 2014) as observed in borane clusters.…”
Section: Limits Of the Carbonyl Cluster Seriesmentioning
confidence: 99%